PRESTASI BELAJAR MAHASISWA DITINJAU DARI DIMENSI REGULITAS DALAM KURIKULUM MERDEKA - Darsi; Rasmita (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to analyze student learning achievement in terms of the regularity dimension. The regularity dimension includes aspects such as discipline, responsibility, and self-regulation in the learning process. The research method used is a quantitative approach with a descriptive-correlational research type. The sample in this study was 150 students from various study programs at a university. Data collection was carried out through questionnaires and documentation of student academic grades. The results showed that there is a positive and significant correlation between the regularity dimension and student learning achievement. Students with a high level of regularity tend to have better learning achievement compared to students with a low level of regularity. The regularity dimension that has the most influence on learning achievement is responsibility and self-regulation in the learning process. The higher the level of student responsibility and self-regulation, the better the learning achievement achieved. The implication of this research is the need to strengthen student character development programs that focus on increasing regularity, especially the aspects of responsibility and self-regulation. This is expected to contribute to the continuous improvement of student learning achievement.